Efforts For Forming Religious Character Through The Addition Of Religious Activities - Wanda Nurjanah; Ai Fatimah Nur Fuad; Muhammad Abdullah Darraz (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2024)
This research aims to describe efforts to build religious character through habituation to religious activities at MAN 19 Jakarta. This research uses a qualitative methodology using descriptive analysis tools and field research methodology. The research involved participants from MAN who were actively involved in religious activities, including observations, and interviews with teachers and students. The findings of this investigation add significantly to our understanding of how religious education at MAN can be an effective means of forming students' religious character. The practical implications can be used to strengthen character through religious activities that are carried out, namely by cultivating the 5S (Greetings, smiles, greetings, politeness and politeness) along with P5 in the independent curriculum, the practice of Duha prayers which teaches them to be obedient and serious in worship and reading activities Al-Qur'an before learning begins